Comparative Analysis of Linked Unsupervised based Feature Selection Framework for Social Media Data - Pradeepa, T; Shanmugapriya, B (International Journal of Computer Sciences and Engineering, 2025)
The explosive usage of social media produces massive amount of unlabeled and high- dimensional data. Feature selection has been proven to be effective in dealing with high-dimensional data for efficient learning and data mining. Unsupervised learning has been proven to be a powerful technique in unsupervised feature selection, which allows embedding feature selection into the classification (or regression) problem. In literature several numbers of feature selection methods such as supervised feature selection algorithms and unsupervised feature selection methods have been proposed to select dimensional feature in the social network. When compare to supervised methods ,unsupervised feature selection methods performs well since it perform operation without label information .But unsupervised feature selection is particularly difficult due to the definition of relevancy of features becomes unclear. To solve this problem , in this paper study a unsupervised feature selection algorithm the concept of pseudo-class labels to guide extracting constraints from link information and attribute- value information, resulting in a new Linked Unsupervised based feature selection framework (LUFS), for linked social media data. LUFS examine the differences between social media data and traditional attribute value data; investigate how the relations extracted from linked data can be exploited to help select relevant features for linked social media data. Furthermore, social theories are developed by sociologists to explain the formation of links in social media. Experimental results on various social media datasets demonstrate the effectiveness of the proposed framework LUFS is compared with existing schemas in terms of accuracy and Normalized Mutual Information (NMI). Design and conduct systemic experiments to evaluate the proposed framework on data sets from real-world social media websites.